Systematic literature review: Supervision of Inclusive Education in Basic Education Units (Early Childhood Education and Primary Schools) - Sari, Meyritha Trifina; Burhanuddin, Burhanuddin; Supriyanto, Achmad (Proceedings Series of Educational Studies, 2024)
In developing countries, the treatment of children with special needs involves a holisticand interrelated approach, engaging parents, local health services, and educational institutions. However, preliminary studies reveal two major issues: (1) the absenceof specific supervision guidelines for inclusive education programs, and (2) supervisors' lack of knowledge on how to assist inclusive education, despite socialization efforts. Inclusive schools, both public and private, implement these programs based on school autonomy. This research aims to identify supervisory strategies that are appropriate or adaptabletothe current conditions of inclusive education in Indonesia. It employs the SystematicLiterature Review (SLR), focusing on a comprehensive review and analysis of relevant literature. The study examines 26 sources from databases such as Open Knowledge, Google Scholar, and DOAJ, covering publications from 2014 to 2024. The findingsindicate that the most common supervisory strategy is the adaptation of regular school supervision practices, with focus group discussions involving supervisors and teachersbeing the primary data collection technique. The main strategy used by supervisors isadapting practices from previous regular education programs. Keywords: Inclusive Education, Supervision, Children with Disabilities, Schools